Actualization of Puputan War Spirit to Strengthen Adversity Quotient in Young Generation in the Global Era - I Wayan Putra Yasax; `R. Ahmad Purnawibawa; Ketut Sedana Arta; Alif Alfi Syahrin (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2023)
This study is motivated by the development of the millennial generation, which tends to be weak in the adversity quotient. Conditions where the younger generation is very vulnerable and quickly gives up because they do not have the resilience to the conditions or problems they face. The problem studied is to provide an understanding of the concept of the adversity quotient, the spirit of the Puputan War as a model for strengthening the adversity quotient, and its implementation. The method used in this study is a qualitative approach to the literature review model, which examines various sources from books, articles, and also websites that discuss research problems. The study found that the millennial generation has a low adversity quotient attitude. The younger generation is now accustomed to instant culture due to technological developments. This impacts their vulnerability when they find problems, and they tend to take adverse actions such as suicide, plagiarism, theft, and other harmful things. However, this condition can be prevented by giving examples of the spirit of bellows war that was carried out by the Balinese people in fighting the invaders with all their limitations, and they were still able to fight to the last drop of their blood. The values of the Puputan war character that can be taken as adversity quotient reinforcement include unyielding spirit, hard work, willingness to sacrifice, nationalism and love of the motherland, loyalty, and religious values. These values can be used as a character education model taught in schools through history lessons to strengthen the adversity quotient, which is currently decreasing among millennials. Its implementation can be carried out in the Project to Strengthen the Pancasila Student Profile, a mandatory sub-material in the independent curriculum being implemented at this time.